2017
DOI: 10.3390/electronics6030057
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Arrays for Line-of-Sight Massive MIMO: Half Wavelength Is Not Enough

Abstract: Abstract:The aim of this paper is to analyze the array synthesis for 5 G massive MIMO systems in the line-of-sight working condition. The main result of the numerical investigation performed is that non-uniform arrays are the natural choice in this kind of application. In particular, by using non-equispaced arrays, we show that it is possible to achieve a better average condition number of the channel matrix and a significantly higher spectral efficiency. Furthermore, we verify that increasing the array size i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…The first example refers to a 9×9 uniform square array with an interelement spacing equal to 3/4 λ [9]. This implies that the array side is lower than 7 cm, making it suitable for usage on typical commercial smartphones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first example refers to a 9×9 uniform square array with an interelement spacing equal to 3/4 λ [9]. This implies that the array side is lower than 7 cm, making it suitable for usage on typical commercial smartphones.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, the design of an antenna array has to deal with two main problems: the development of the physical system (i.e., the geometry of the array and the selection of the radiating elements) [9,10], and the evaluation of the excitations that better satisfy the pattern synthesis requirements [11,12]. For this second task, several algorithms have been developed considering the geometry of the array, the shape of the desired pattern, and the degrees of freedom that characterize the array excitations [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…g NCC max = N r (10) Equations (9) and (10) indicate that there is a maximum value for the combining improvement that depends exclusively on the number of combined beams. Results given in Table 4 and in reference [36] comply with these limits.…”
Section: Environmentmentioning
confidence: 99%
“…Massive multiple-input-multiple-output (MIMO) techniques [7,8] will have to be implemented in 5G systems to deal with the data traffic growth. Base stations are expected to be equipped with a very high number (even hundreds) of antennas [9] that will serve simultaneously several terminals, which will be also equipped with a number of antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Antenna arrays are one of the most important technologies that allows responding to the challenges of the close future communication systems, particularly in the 5G and IoT frameworks [1][2][3][4]. In this perspective, the use of sparse, non-regular, arrays is particularly appealing, since it has been shown that a sparse array is often capable of achieving the same performance of regular lattice ones, with a much lower number of radiating elements, and a strong reduction of the issue of grating lobes.…”
Section: Introductionmentioning
confidence: 99%